Outlier detection in stream data by machine learning and feature selection methods - Koupaie, Hossein Moradi (2013)
In recent years, intrusion detection has emerged as an important technique for network security. Machine learning techniques have been applied to the field of intrusion detection. They can learn normal and anomalous patterns from training data and via Feature selection improving classification by searching for the subset of features which best classifies the training data to detect attacks on computer system. The quality of features directly affects the performance of classification. Many feature selection methods introduced to remove redundant and irrelevant features, because raw features may reduce accuracy or robustness of classification. Outlier detection in stream data is an important and active research issue in anomaly detection. Most of the existing outlier detection algorithms has less accurate because use some clustering method. Some data are so essential and secretary. Therefore, it needs to mine carefully even if spend cost. This paper presents a framework to detect outlier in stream data by machine learning method. Moreover, it is considered if data was high dimensional. This method is more accurate from other preferred models, because machine learning method is more accurate of other methods.